GAMBARAN KREATIVITAS PADA ANAK USIA 4-5 TAHUN MELALUI PEMBELAJARAN METODE STEAM BERBASIS LOOSE PARTS DI TAMAN ANAK SANGGAR ANAK ALAM - Septiani Hapidah, Sri Ernawati, Dhian Riskiana Putri (Universitas Sahid Surakarta, 2025)
Creativity in early childhood is the ability to explore theenvironment, solve problems in unique and imaginativeways, and generate new ideas. The study aims to determine how the loose parts-based STEAM method is in increasing the creativity of children aged 4-5 years at the Taman AnakSanggar Anak Alam. This research used a qualitative method with a case study approach. Data were collectedusing observation, interview, and documentation techniques.There were 8 research informants, namely, facilitators, PKBM chairpersons, and parents. The results indicate that there are several descriptions that increase children's creativity through the loose parts-based STEAM method, namely: A supportive environment, exploration through loose parts, development of curiosity and problem-solving, collaboration and role-playing, integration of STEAM concepts, and the role of facilitators.